PERBANDINGAN HASIL BELAJAR PESERTA DIDIK DENGAN MENGGUNAKAN MODEL PEMBELAJARAN TGT (TEAM GAME TOURNAMENT) DAN MODEL PEMBELAJARAN GI (GROUP INVESTIGATION) - Rosa Rosanti; Rendra Gumilar; Ati Sadiah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Based on the background in this study, at SMA Negeri 2 Tasikmalaya, economic learning still uses teacher content learning, namely meaningful learning for teachers in the classroom. Teachers are usually more dominant as learning centers and students are less active when deepening the material. As a result, many students still get low learning outcomes. In this situation, the researcher experiments using the cooperative learning model, the researcher will conduct a study that compares the learning outcomes of students with two cooperative learning models, namely the TGT (Team Game Tournament) and GI (Group Investigation) cooperative learning models. The research method used in this study is an experimental method, which is a method that has the purpose of testing the relationship between one variable and another. The research design used by the researcher is a 2x2 factorial design. The population in this study is all students of class X of SMAN 2 Tasikmalaya Even Semester for the 2023/2024 school year, as many as 12 classes with a total of 430 students. The sample used in this study is 2 classes where classes X - 11 are Experiment A class and X-12 is Experiment B class. Students who have high abilities are better off using the TGT (Team Game Tournament) type cooperative learning model, while students who have low abilities are better off using the GI (Group Investigation) type learning model). The learning outcomes of students who are taught with the TGT (Team Game Tournament) type cooperative learning model are better than the learning outcomes of students who are taught with the learning model (Group Investigation) on Bank and Other Financial Institutions materials in class X of SMA Negeri 2 Tasikmalaya.